A National Survey on the Clinical Practice Patterns of Korean Medicine Doctors for Attention Deficit Hyperactivity Disorder (ADHD) in Children and Adolescents - Jihong Lee (MDPI AG, 2023)
To alleviate the symptoms of attention deficit/hyperactivity disorder (ADHD) in children and reduce the side effects of psychostimulants, parents are opting for complementary and alternative medicine as a therapeutic option. Korean medicine (KM) has been used by Korean medicine doctors (KMDs) to treat ADHD with herbal medication and acupuncture. This study aimed to conduct a cross-sectional survey on the clinical practice patterns of KM for ADHD in children targeting KMDs. The questionnaire included aspects related to patient characteristics, diagnosis, treatment modalities, and perceptions regarding KM. Questionnaires were distributed to all KMDs via e-mail, and the online surveys were conducted from 1 to 15 February 2023. A total 2.1% of KMDs (n = 537/25,574) completed the survey. The predominant diagnostic pattern identification employed was "depressed liver qi transforming into fire" (19.8%). Herbal medicine (HM) was the most common treatment (44.2%). The most frequently used HM prescriptions were Ondam-tang (16.9%), Eokgan-san (15.7%), and Sihogayonggolmoryeo-tang (14.4%). KMDs recognized HM as the most effective among the KM treatments (54.3%). The results of this study elucidate the current clinical practice patterns of KM for ADHD. Based on these findings, a treatment protocol can be developed to provide optimized KM treatment services to patients with ADHD.